Adverse pregnancy outcomes during the COVID-19 lockdown. A descriptive study - Eman F. Badran; Rula M. Darwish; Yousef Khader; Rama AlMasri; Mira Al Jaberi; Mohammad AlMasri; Farah AlSa'di; Leen abu Yosef; Noor al-Badaineh (BMC, 2021)
Abstract Background The ongoing spread coronavirus disease worldwide has caused major disruptions and led to lockdowns. Everyday lifestyle changes and antenatal care inaccessibility during the coronavirus disease 2019 (COVID-19) pandemic have variable results that affect pregnancy outcomes. This study aimed to assess the alterations in stillbirth, neonatal-perinatal mortality, preterm birth, and birth weight during the COVID-19 national lockdown. Methods We used the data from the Jordan stillbirths and neonatal death surveillance system to compare pregnancy outcomes (gestational age, birth weight, small for gestational age, stillbirth, neonatal death, and perinatal death) between two studied periods (11 months before the pandemic (May 2019 to March 2020) vs. 9 months during the pandemic (April 2020 to March 1st 2020). Separate multinomial logistic and binary logistic regression models were used to compare the studied outcomes between the two studied periods after adjusting for the effects of mother's age, income, education, occupation, nationality, health sector, and multiplicity. Results There were 31106 registered babies during the study period; among them, 15311 (49.2%) and 15795 (50.8%) births occurred before and during the COVID-19 lockdown, respectively. We found no significant differences in preterm birth and stillbirth rates, neonatal mortality, or perinatal mortality before and during the COVID-19 lockdown. Our findings report a significantly lower incidence of extreme low birth weight (ELBW) infants (<1kg) during the COVID-19 lockdown period than that before the lockdown (adjusted OR 0.39, 95% CI 0.3-0.5: P value <0.001) Conclusions During the COVID-19 lockdown period, the number of infants born with extreme low birth weight (ELBW) decreased significantly. More research is needed to determine the impact of cumulative socio-environmental and maternal behavioral changes that occurred during the pandemic on the factors that contribute to ELBW infants.